A integrated process for nitrilase-catalyzed asymmetric hydrolysis and easy biocatalyst recycling by introducing biocompatible biphasic system. Issue 1 (January 2021) - Zou, Shuping; Hua, Dengen; Jiang, Zhentao; Han, Xin; Xue, Yaping; Zheng, Yuguo
Graphical abstract: Highlights: Use of a biphasic system to enhance nitrilase-catalyzed asymmetric hydrolysis. Whole-cell nitrilases still retained >85% activity after 7 cycles reaction. The efficient integrated process was feasible on a 2-L preparative scale. R -CMA yield of 91.3% was achieved with a space–time yield of 746.4 g∙L −1 ·d −1 . Abstract: The whole-cell nitrilase-catalyzed asymmetric hydrolysis of nitriles is a green and efficient preparation approach for chiral carboxylic acids, but often suffers from toxicity and cell lysis from organic substrates. In this work, a novel integrated process for whole-cell nitrilase-catalyzed asymmetric hydrolysis was developed for the first time by introducing a biocompatible ionic liquid (IL)-based biphasic system. The whole-cell nitrilases displayed an outstanding stability and recyclability in the biphasic system and still retained > 85% activity even after 7 cycles reaction. A preparative-scale fed-batch hydrolysis of o -chloromandelonitrile to ( R )- o -chloromandelic acid ( R -CMA) was performed using the integrated process. The results revealed a yield of 91.3% and a space–time yield of 746.4 g·L −1 ·d −1, which are currently the highest reported values for R -CMA biosynthesis. The proposed integrated process avoids substrate inhibition, facilitates the reusability of whole-cell nitrilases, and thus shows great potential for the sustainable production of chiral carboxylic acids.